Deoiling and regeneration efficiencies of spent bleaching clay - Abd. Wafti, Nur Sulihatimarsyila; Cheah, Kien Yoo; Chuah, Teong Guan; Siew, Wai Lin; Choong, Thomas Shean Yaw (Science Publications, 2010)
Problem statement: Disposal and reuse of Spent Bleaching Clay (SBC) from palm oil processing industry is a problem of growing importance. The residual oil in the SBC can be recovered using hexane as solvent. Approach: In this study, the effect of different solid to solvent ratio on the deoiling efficiency of SBC samples from palm oil refinery and palm kernel refinery were studied. The amount of extracted oil and deoiling efficiency for both types of SBC increases as the solid to solvent ratio is decreased. Results: All the extracted oils, irrespective of the amount of solvent used, have poorer quality than crude oil and may be difficult to be refined to good quality and stability. Conclusion: The deoiled SBC treated using different solid to solvent ratio gave almost similar regeneration efficiency i.e., about 80% for bleaching of CPO and not more than 30% for bleaching of CPKO.